A novel in situ methodology for visual detection of Clostridium perfringens in pork harnessing saltatory rolling circle amplification. (June 2021) - Milton, Arockiasamy Arun Prince; Momin, Kasanchi M.; Priya, Govindarajan Bhuvana; Ghatak, Sandeep; Gandhale, Pradeep N.; Angappan, Madesh; Das, Samir; Sen, Arnab
Abstract: Clostridium perfringens ( C. perfringens ), a prolific toxin-producing anaerobe is an important foodborne pathogen with a huge public health concern. Rapid and on-site detection of C. perfringens is of specific importance in developing countries. In the present study, saltatory rolling circle amplification (SRCA) assay was developed for culture-independent, rapid and visual detection of C. perfringens and evaluated in meat with pork as a model. The specificity of the SRCA assay was ascertained by using 62 C. perfringens and 18 non- C. perfringens strains. The analytical sensitivity of the developed SRCA, conventional and real-time PCR assays were 80 fg, 800 fg and 800 fg DNA per tube, respectively. The limit of detection of the SRCA assay was 80 CFU/g of pork in the absence of enrichment and 8 CFU/g after short enrichment of 6 h. The detection limits of 80 CFU/g and 8 CFU/g of pork were attained within 120 min and 8 h, respectively. Real-world or field relevancy of the developed assay was evaluated by screening 82 raw and processed pork samples. As the developed assay is simple, user-friendly, cost-effective and sophisticated-equipment free, it would be more suitable for on-site testing of C. perfringens in foods. To our information, this is the first report to apply SRCA for the detection of C. perfringens. Graphical abstract: Image 1 Highlights: A novel SRCA assay was developed for rapid and visual detection of Clostridium perfringens in meat. The analytical sensitivity of the SRCA assay (80 fg) was 10 fold more than the conventional and real-time PCR. The detection limit of 80 CFU and 8 CFU per gram of meat was attained within 120 min and 8 h, respectively. This is the first report to use SRCA for the detection of C. perfringens .